Laparoscopic Gastrostomy Placement in Children Has Few Major, but Many Minor Early Complications - Kvello, Morten; Knatten, Charlotte Kristensen; Bjørnland, Kristin (European Journal of Pediatric Surgery, 2019)
Introduction Laparoscopic gastrostomy (LAPG) is an increasingly popular alternative to more traditional gastrostomy techniques. This study evaluates early postoperative complications following LAPG and investigates risk factors for gastrostomy complications.Materials and Methods Retrospective study of patients <16 years undergoing LAPG from 2005 to 2018. Early postoperative complications (<30 days) were grouped as gastrostomy-related or general and graded according to the Clavien-Dindo classification for surgical complications.Results A total of 104 patients, of which 54 (52%) had neurological impairment (NI), were included. Median age and weight were 1.2 years (1 day–15.2 years) and 8.9 kg (3.4–36), respectively. Operating time was median 37 minutes (19–86) and shorter in the second half of the patients (46 vs. 35 minutes, p = 0.04). A total of 40 (38%) patients experienced 53 gastrostomy-related complications. Of these, seven complications needed surgical treatment; severe leakage (2), too short gastrostomy button (1), feeding difficulties (1), gastric outlet obstruction (1), omentum trapped in umbilical port sutures (1), and suspected fascial defect (1). Stoma infection and granulation tissue were reported in 13 and 12%, respectively. Tube dislodgement occurred in six patients and was managed with bedside reinsertion in all. Gastrostomy-related complications were less frequent in NI patients (46 vs 22%, p = 0.01).Conclusion LAPG is a safe procedure with few major complications, but a high rate of minor complications. Operating time declined during the study period, and NI patients had fewer gastrostomy-related complications.
Keywords: laparoscopy; gastrostomy; enteral nutrition